Comparative Assessment of In Vitro Effect of Three Fluoride Releasing Agents on Enamel Demineralization around Orthodontic Brackets - Jasim, Esraa S; Garma, Noor M; Thyab, Samer A (Journal of Baghdad College of Dentistry, 2016)
Background: White spot lesion considered as irreversible tooth demineralization presenting challenge to orthodontists during treatment schedules, fluoride was the most successfully used measure to overcome this challenge. Materials and method: A total of forty sound human permanent premolars were used in the present study and categorized into four groups, in one group the teeth were bonded with stainless steel brackets using Resin-modified glass ionomer cement (RMGIC) and the other three groups the teeth were bonded with light cured composite ResilienceÂ® (Ortho technology Co., USA). Group A; Acidulated phosphate fluoride (APF) topical gel (Mfg by DEEPAK PRODUCTS, INC, USA), fluoride ion 1.23% applied on examine area for four minute. Group B; RMGIC (GC Fuji Ortho LC, GC Corporation/Japan) used as bracket adhesive. Group C; Stannous and sodium phosphate fluoride gel yielding 0.72% fluoride ion (Mfg. for: dental resources DS-8) (0.4% Stannous fluoride, 1% sodium fluoride), was applied daily through the experimental study. D; the control group represents the conventional bonding procedure with no preventive method. The entire labial surfaces except 2 mm gingival to the bracket were isolated by acid resistance varnish. All the teeth were subjected individually during 30 days in to acid challenge cycle. After longitudinal sectioning of the teeth by using a hard-tissue microtome, the depth of the artificial lesion was estimated by taking the average of three penetration depths at the lesion centre under stereomicroscope. Also the enamel surface was classified according to acid etch pattern. Comparisons of the average caries penetration of the groups were submitted to ANOVA and LSD tests. The statistical significance level was set at p â‰¤ 0.05. Results: The results revealed that there were statistically significant differences among the tested groups. With different caries reduction abilities, APF group showed 14%, RMGIC Group 49%, group Stannous and sodium phosphate fluoride 39% depth reduction compared to the control group. Conclusions: While all the groups showed caries reduction by different fluoride agents used in this study, the less average lesion depth was found at group B making the RMGIG the best caries fighting fluoride measure.